Annual Plan, 2001-2002 Part-II Government of Maharashtra - Planning Commission (Planning Commission, 2001)
Abstract Statement indicating sub-sector wise outlay and expenditure Abstract Statement showing the provision for Development Board Abstract Statement indicating outlay on Centrally Sponsored Programme Abstract Statement indicating outlay and expenditure in respect of Tribal Area Sub-Plan Abstract Statement indicating outlay and expenditure in respect of Special Component Plan, Abstract Statement of District Plan outlay Statement indicating outlay and expenditure in respect of 20-Point Programmes.
Government of Maharashtra : Planning Department